Torsion of undescended abdominal testicle in a 16-year-old and its management. Issue 1 (29th January 2020) - Malik, Muhamamd Isfandyar Khan; Abbas, Joshua; Sabri, Shariq; Michael, George; Ellenbogen, Simon
Abstract : A 16-year-old boy attended the Emergency Department with sudden severe right iliac fossa pain and associated vomiting. He denied any urinary symptoms, diarrhoea or testicular pain. On examination, he had a locally tender right iliac fossa with guarding. External genitalia and testicular examination revealed an absent right testicle, the left testicle was not tender. The patient was haemodynamically stable. A clinical diagnosis of acute appendicitis and possible testicular torsion was made and the patient sent for an urgent diagnostic laparoscopy. At laparoscopy, the patient was found to have a torted, non-viable right-sided testicle in the abdominal cavity. On discussion with urology, a decision was made to excise the torted testicle as it was atrophic and had significant malignant potential. The appendix was normal. The patient made an unremarkable recovery and was discharged.